Compensatory Belief in Health Behavior Management: A Concept Analysis - Zhao, Kang; Xu, Xinyi; Zhu, Hanfei; Xu, Qin (Frontiers in Psychology, 2021)
Purpose: This study aimed to identify the exact definition of the concept of compensatory belief and to help clinicians and caregivers to distinguish patients who tend to form such beliefs. Methods: This study is a conceptual analysis based on Walker and Avant’s (2014) strategy. We retrieved studies from existing literature using databases such as PubMed, CINAHL, Wiley, and Web of Science, and extracted information from the results. No date limitations were applied. Results: A total of thirty-five articles were sourced for data extraction. The identified attributes of compensatory belief were as follows: cognitive coping strategy, pleasure without guilt, compensatory behaviors, automatic motivated self-regulatory process, and implicit cognition. The observed antecedents were: failure to resist desire, reluctance, a conflicting motivational state, seeking appropriate balance, and self-image maintenance. The consequences of compensatory belief were lower health-related intentions, justification of unhealthy choices, relief from cognitive dissonance, continued existence of conflict feeling, and poor long-term health. Conclusions: Compensatory belief stems from motivational dissonance or confliction. Despite causing feelings of pleasure and relief, it can negatively impact long-term health. Although compensatory belief is crucial to establish healthy behaviors, it is easily ignored in medical work.